2022
DOI: 10.2186/jpr.jpr_d_22_00103
|View full text |Cite
|
Sign up to set email alerts
|

Designing anterior cantilever resin-bonded fixed dental prostheses based on finite element analysis

Abstract: A resin-bonded bridge (RBB) is a minimally invasive prosthetic treatment option for intact adjacent teeth. However, it is contentious as to whether the mesial or distal adjacent tooth should be used as an abutment. This study aimed to investigate the potential of finite element analysis (FEA) for the selection of abutment teeth and the determination of the optimal design for anterior cantilever RBBs. Methods: Three types of RBBs were designed to simulate loss of the maxillary left lateral incisor. The fixed-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It can be incorporated with different loads in different designs of prostheses to evaluate the effect on the abutment teeth as well as surrounding tissue (16,35). Kihara et al, who used FEA to design an anterior cantilever RBB, concluded that FEA was useful for determining the optimal design of RBB for each patient (15). It is also anticipated that more research on the incorporation of new technology in designing the prosthesis using computer-aided design (CAD) and manufacturing the prosthesis using computeraided manufacturing (CAM) techniques will generate new interest in RBB research in evaluating longevity and publication of the United States and international prosthodontic organisations (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be incorporated with different loads in different designs of prostheses to evaluate the effect on the abutment teeth as well as surrounding tissue (16,35). Kihara et al, who used FEA to design an anterior cantilever RBB, concluded that FEA was useful for determining the optimal design of RBB for each patient (15). It is also anticipated that more research on the incorporation of new technology in designing the prosthesis using computer-aided design (CAD) and manufacturing the prosthesis using computeraided manufacturing (CAM) techniques will generate new interest in RBB research in evaluating longevity and publication of the United States and international prosthodontic organisations (31).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of new technology in prosthesis fabrication, new broad material selection, and improvement of the dental adhesive system and luting cement help prolong the overall longevity of RBB and provide new options for RBB fabrication (12)(13)(14). In addition, the use of three-dimensional finite element analysis helps researchers gain a better understanding of the biomechanical behaviour of the restorations with respect to the different designs and materials used for RBB prior to the clinical study (15,16).…”
Section: Introductionmentioning
confidence: 99%